New challenges and problems of the nancial market in the open bank system conditions - S. S. Galazova; L. R. Magomaeva (Управление)
The main trends in the development of the global financial market in conditions of active development of open digital banking, which determines new opportunities and challenges for the creation of innovative banking and financial products are revealed. The key stages of “financial repression”, which predetermined new challenges and problems for the traditional model of the financial market, are considered. The main difficulties and problems connected with the transition from the traditional banking model to the Open Banking Standard model are substantiated. The analysis proves that further development of the financial market dictates the need to increase efficiency and reduce costs in the development of next-generation digital services. In this regard, the widespread introduction of Open Banking Standard will create new products for the financial market. The implementation of Open Banking Standard in real time will allow to open access for the consumer to more personalized information resources, and services will be provided through a secure open service in order to more effectively manage personal finances. Today, many small and medium-sized companies use third-party commercial development for accounting purposes, but they have to enter transaction data manually. The practical use of Open Banking Standard will allow the consumer not only to receive data in real time, but will also partially solve the problem of gaining access to more personalized information resources for making banking decisions. Also, clients will be able to offer better loan terms, as credit institutions will be able to analyze its transaction data to determine the level of the borrower’s risk.